Elka in njen dom - Pisanec, Anuša (Etnolog. Nova vrsta (Ljubljana), 2008)
The article analyses the attitude of the Roma Elka Strojan - whom we visited at her temporary accommodations in Roje, Šentvid, where she lived with her family, in late August 2007 - to (domestic and foreign) space, her experience and use of the physical environment where she belonged earlier, and her attachment to a given place. We were interested in the construction of her home space and the crucial process proved to be the importance Elka attributed to her own land - expressed in her story as her home. Another special point of interest was the way of living of the Roma Strojan family in relation to the environment (nature) and space, that is their use of natural resources as the key element of their survival tactics and gainful activities.
Keywords: Strojan, Elka; ethnology; etnologija; Romi; dom; antropologija prostora